NON DISCLOSURE AGREEMENT UNDER LABOR CODE 2012 - Nguyễn Văn Tố Hữu (Tạp chí Khoa học Đại học Đà Lạt, 2020)
Non disclosure agreement is not only an important content but also a special agreement on the labor relation between employees and employers. However, the Vietnamese labor law does not guide to this problems. This paper to present, analyze current regulations’ limitations as well as to provide solutions in particular about non disclosure agreement